Evaluation of the Relationship between T2*CMR and Cardiac Depolarization and Repolarization Parameters in Beta-Thalassemia Patients - yazdan ghandi; Bita Ghahremani; Aziz Eghbali; Parsa Yousefichaijan; Masoud Bahrami (Journal of Kerman University of Medical Sciences, 2024)
Background: Cardiac iron overload causes severe cardiac complications and is a leading cause of death in beta-thalassemia major patient. T2*CMR can detect preclinical cardiac iron overload. We evaluated the ability of 12-lead electrocardiographic atrial and ventricular depolarization and repolarization parameters to predict cardiac iron loading in TM.Materials and methods: This cross-sectional study was conducted on Patients with Beta thalassemia major; all participants underwent standard 12 lead electrocardiogram during a single study visit and the depolarization and repolarization parameters of ECG were measured and compared to the cardiac iron level detected by T2*CMR, with a detectable cardiac iron cutoff of T2*less than 20 ms.Results: A total of 26 patients (mean 26.19 years old, 34.62% male) were included. Mean T2*CMR values were 21.53 ms (46.15% <20 ms, 53.85% ≥20 ms). Among ECG parameters, only Pwd, QTc and QTcd (p: 0.026, 0.030, and 0.006 respectively) were significantly prolonged in patients with T2* < 20 ms compared to patients with T2*≥ 20 ms. There was a statistically negative Correlation between T2 * CMR and Pwd and QTcd (p: 0.028, and 0.021 respectively). Moreover, no correlation was found between Tp-e, Tp-e d, JTc, JTcd, Tp-e/QT, Tp-e/JT, Tp-e/JTc and T2* values.Conclusions: PWD and QTcd can be used as an alternative to T2*CMR to predict cardiac iron load levels in patients with beta thalassemia major.